Proses Berpikir Kritis Siswa dalam Pembelajaran Diferensiasi Ditinjau dari Gaya Belajar - Abduloh Ridwan (CV. Intake Pustaka, 2026)
This article aims to describe students' critical thinking processes in differentiated learning, examined through learning styles using a phenomenological approach. The focus of this study is on the experiences of students with visual, auditory, and kinesthetic learning styles when engaging in differentiated learning activities. The research findings indicate that critical thinking develops through different cognitive pathways according to learning preferences. Visual learners tend to more easily build critical reasoning through visual representations such as diagrams or concept maps. Auditory learners strengthen critical thinking through discussions and reflective dialogues, while kinesthetic learners develop critical thinking through hands-on experiences and observation. These findings suggest that differentiation in learning can function as a cognitive bridge, providing all students access to develop critical thinking through different approaches, with a learning design that takes into account multi-representations, dialogue, and experience-based activities.